Perception and Interpretation of Contrastive Pitch Accent During Spoken Language Processing in Autistic Children - Pumpki Lei Su; Duane G. Watson; Stephen Camarata; James Bodfish (Languages, 2025)
Although prosodic differences in autistic individuals have been widely documented, little is known about their ability to perceive and interpret specific prosodic features, such as contrastive pitch accent—a prosodic signal that places emphasis and helps listeners distinguish between competing referents in discourse. This study addresses that gap by investigating the extent to which autistic children can (1) perceive contrastive pitch accent (i.e., discriminate contrastive pitch accent differences in speech); (2) interpret contrastive pitch accent (i.e., use prosodic cues to guide real-time language comprehension); and (3) the extent to which their ability to interpret contrastive pitch accent is associated with broader language and social communication skills, including receptive prosody, pragmatic language, social communication, and autism severity. Twenty-four autistic children and 24 neurotypical children aged 8 to 14 completed an AX same–different task and a visual-world paradigm task to assess their ability to perceive and interpret contrastive pitch accent. Autistic children demonstrated the ability to perceive and interpret contrastive pitch accent, as evidenced by comparable discrimination ability to neurotypical peers on the AX task and real-time revision of visual attention based on prosodic cues in the visual-world paradigm. However, autistic children showed significantly slower reaction time during the AX task, and a subgroup of autistic children with language impairment showed significantly slower processing of contrastive pitch accent during the visual-world paradigm task. Additionally, speed of contrastive pitch accent processing was significantly associated with pragmatic language skills and autism symptom severity in autistic children. Overall, these findings suggest that while autistic children as a group are able to discriminate prosodic forms and interpret the pragmatic function of contrastive pitch accent during spoken language comprehension, differences in prosody processing in autistic children may be reflected not in accuracy, but in speed of processing measures and in specific subgroups defined by language ability.